Fabrication and characterization of in vitro 2D skin model – An attempt to establish scaffold for tissue engineering. (October 2021) - Pandiyan, Rajesh; Sugumaran, Abimanyu; Samiappan, Sumathi; Sengottaiyan, Parameshwaran; Ayyaru, Sivasankaran; Dharmaraj, Selvakumar; Ashokkumar, Veeramuthu; Pugazhendhi, Arivalagan
Graphical abstract: Highlights: Successive 2D-skin scaffold was prepared from biomaterials. FE-SEM image shows the high degree of viable epidermis formation. 2D-skin shows significant degree of swelling index and enzymatic degradation. Pus forming bacteria were eliminated by cell viability test treated upon 2D skin. K. pneumonia and S. aureus shows 61.94 % 68.45 % of inhibition respectively. Abstract: In the recent decade, tissue engineering has achieved noteworthy progress in artificial skin preparation. The present study is intended to harvest 2D skin from Bombyx mori cocoons and collagen type I with chicken endothelial cell culture for alleviating skin diseases like cancer. The Artificial 2D Skin is fabricated by seeding the endothelial cell, fibroblast and keratinocytes embedded in the silk sponge for 21 days, which results in a 2D skin. The fabricated 2D skin scaffold is subjected to material characterization and evaluated by UV absorption, FTIR, FESEM, swelling index, enzymatic degradation and antibacterial activity. The UV absorbance of sericin, fibroin and collagen are found at 215–240, 260−290 and 300 nm respectively. The results of FT-IR spectrum confirms the presence of proteinaceous substances. Moreover, FESEM shows a high degree of viable epidermis formation. The swelling index and enzymatic degradation is found as 30 %, 26.5 % respectively. The cell viabilitytest performed on different pus-forming bacteria which exhibited antibacterial property significantly at p<0.001 . E. coli and has deprived viable conditions whencomparing with other organisms. From the above results, it is inferred that the 2D skin is equivalent to human skin which could be utilized for various skin therapy and tissue engineering.